Intraoperative quantitative mitral valve analysis using optical tracking technology - Engelhardt, Sandy; Wolf, Ivo; Maisary, Sameer al-; Schmidt, Harald; Meinzer, Hans-Peter; Karck, Matthias; De Simone, Raffaele (The annals of thoracic surgery, 2016)
Purpose - Analysis of mitral valve morphology during reconstruction is routinely based on visual assessment and subjective, poorly reproducible measurements. We prove the feasibility of a new intraoperative system for quantitative mitral valve analysis. - Description - The proposed computer-based assistance system enables accurate intraoperative localization of anatomic landmarks on the mitral valve apparatus using optical tracking technology. Measurement and visualization strategies were specifically developed and tailored for mitral valve operations. - Evaluation - The feasibility of intraoperative quantitative measurements was successfully shown for 9 patients. Precise geometric descriptions of the valve were obtained and adequately visualized, providing valuable decision support during the intervention. The mean annular area obtained from the intraoperative measurements was 736 ± 266 mm2, in good agreement with the mean area of the implanted prosthetic rings of 617 ± 124 mm2, which are slightly smaller due to annular downsizing. Comparison with preoperative three-dimensional echocardiography revealed differences between the beating heart, with transverse and septolateral annular diameters of 40.6 ± 15.4 mm and 41.2 ± 8.2 mm, and the intraoperative cardioplegic condition, with corresponding diameters of 34.3 ± 6.9 mm and 27.4 ± 5.6 mm. - Conclusions - Mitral valve analysis by optical tracking represents a unique technologic advance in intraoperative assessment, providing the surgeon with an extended quantitative perception of surgical target. This technology promotes a major philosophical change from an empirical procedure toward a quantitatively predictable modern reconstructive operation.